2011
DOI: 10.1016/j.ultrasmedbio.2011.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Focused-Ultrasound Disruption of the Blood-Brain Barrier Using Closely-Timed Short Pulses: Influence of Sonication Parameters and Injection Rate

Abstract: Blood brain barrier disruption (BBBD) shows promise for drug delivery in the brain, however optimal parameters for disruption have yet to be firmly established. Previous work has shown that BBBD can be achieved using bursts comprised of microsecond length pulses at 50% duty cycle in order to eliminate standing waves and variability. The capabilities and limitations of this sort of pulse sequence comprising short bursts were examined. Ultrasound induced BBBD was performed in 28 rats using Definity contrast agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 22 publications
5
95
1
Order By: Relevance
“…due to the large focal spot size at low frequency and high pressure requirements at high frequency [23]. In addition to frequency, other ultrasound parameters including burst duration have been shown to positively correlate with BBB opening [2426]. With respect to pulse repetition frequency, it has been suggested that adequate time is required to allow time for reperfusion of the microbubbles [27] however, changes in burst repetition frequency did not affect changes in BBB permeability [24].…”
Section: Focused Ultrasound-mediated Bbb Openingmentioning
confidence: 99%
“…due to the large focal spot size at low frequency and high pressure requirements at high frequency [23]. In addition to frequency, other ultrasound parameters including burst duration have been shown to positively correlate with BBB opening [2426]. With respect to pulse repetition frequency, it has been suggested that adequate time is required to allow time for reperfusion of the microbubbles [27] however, changes in burst repetition frequency did not affect changes in BBB permeability [24].…”
Section: Focused Ultrasound-mediated Bbb Openingmentioning
confidence: 99%
“…LIPUS may damage the structural integrity of the membrane of tumor cells mechanically via sonoporation (16)(17)(18)(19). In our experiment, the effect of proliferation could be excluded by reason of detecting M value immediately after irradiation.…”
Section: Optimum Irradiation Of Reversing Mdr Of Sk-n-sh/mdr1mentioning
confidence: 99%
“…The use of a conformal array of focused transducer elements allows for tight focusing at lateral targets in the brain, with sufficient acoustic pressures for a number of therapies involving relatively short ultrasound pulses, including BBB opening, where sonications were performed at a pressure of 0.54 MPa (O’Reilly et al 2011), which is within the range of acoustic pressures presented in Table 1. These studies were performed at 1.18 MHz, however, and the required pressures at 500 kHz could be different as a result.…”
Section: Discussionmentioning
confidence: 99%